Conference report: II Research Conference of the Faculty of Engineering of the year 2020. - Arrieta Orozco, Orlando (2021)
This Special Volume is a report of the congress of the II Research Conference of the Faculty of Engineering of the University of Costa Rica. The conference took place virtually between 10 and 12 November 2020. The contribution of abstracts to this Special Volume was voluntary by the speakers, therefore, in this one 53 of 70 papers that were presented during the event are exposed. This report compiles the extended summaries of the presentations in the 10 thematic areas that were addressed in the II Research Conference.